Financial Literacy and Intertemporal Arbitrage - Luis Oberrauch; Tim Kaiser (ZBW - Leibniz Information Centre for Economics, 2020)
We study the role of financial literacy for inter-temporal decision-making using an adapted version of the Convex Time Budget Protocol (Andreoni and Sprenger 2012). While we find no evidence of dynamically inconsistent preferences in the aggregate, we document substantial heterogeneity in choice-patterns and estimated parameters at the individual-level: We find that subjects with higher levels of financial literacy are more likely to make patient inter-temporal choices, to allocate the entire budget to a single payment-date, allocate the entire budget to corner choices as interest rates increase, and to show individual discount factors which are in line with extra-experimental market rates. At the same time, financial literacy is uncorrelated with choice consistency and estimated individual error parameters. These results serve as suggestive evidence for inter-temporal arbitrage among financially literate respondents, thereby revealing a potential confound in time-preference elicitation tasks relying on time-dated monetary rewards.
Keywords: G53; D15; D91; 330; Intertemporal choice; financial literacy; narrow bracketing; arbitrage